Macromechanics study of stable fatigue crack growth in Al–Cu–Li–Mg–Ag alloy. Issue 2 (28th June 2016) - Akhtar, N.; Wu, S. J.
Abstract: This study was made on a fresh variety of Al–Li base alloy to investigate the role of ageing precipitates and microstructure dimensions in the fatigue crack growth resistance. The fatigue crack growth rate was measured in three different states of the material (i.e. base metal in T8 condition, friction stir weld and laser beam weld in full‐aged condition). Metallurgical analysis showed that the base metal in T8 temper is precipitation hardened by an equivalent amount of δ ′ (AL3 Li), T 1 (AI2 CuLi) and θ ′ (AI2 Cu) precipitates. The friction stir weld retained the morphology of strengthening precipitate; however, coarsening of Cu containing precipitates has occurred. On the other hand, laser beam weld showed a different type of CuAl phase morphology, which is characteristic of cast metal. The results of fatigue tests confirmed that fatigue crack growth resistance largely depends on microstructural features, specifically the strengthening phases. The fatigue crack resistance was in the order of base metal > laser beam weldment > friction stir weldment. The CuAl phase played a vital role in the crack closure of the laser beam weldment, thus enhancing the fatigue life as compared with the friction stir weldment, which was evident from the plot between log of da/dN (crack growth in each cycle) and log of Δ K (stress intensity range).